The Bad Guys in intergalactic gas - Blabey, Aaron (New York, NY Scholastic, Inc, 2018)
"The bad news? The world is ending. The good news? The Bad Guys are back to save it! Sure, they might have to "borrow" a rocket. And there might be something nasty in one of the spacesuits. And Mr. Piranha miiiiight have eaten too many bean burritos. Surviving this mission may only be one small step for man, but it's one giant leap for the Bad Guys"--
English stories
For primary school age
Keywords: Animals -- Juvenile fiction; Rescues -- Juvenile fiction; Supervillains -- Juvenile fiction; Animals -- Fiction; Graphic novels; Rescues -- Fiction; Supervillains -- Fiction; Children's stories; Animals; Humorous stories; JUVENILE FICTION -- Action & Adventure -- General; JUVENILE FICTION -- Animals -- General; JUVENILE FICTION -- Humorous Stories; Rescues; Supervillains; Fiction; Graphic novels; Graphic novels; Humorous fiction; Humorous fiction; Humorous fiction; Juvenile works